Answer:
( x / 3 ) + 1.67 = y
Step-by-step explanation:
For an inverse function, all you have to do is switch the y ( f(x) ) and the x. Then, you can solve for y.
So,
x = 3y - (7/2)
Move the (7/2) to the other side
x + (7/2) = 3y
Now, divide by 3 on both sides
( x + (7/2) ) / 3 = y
You can write it like that or if you want you can separate the x and the (7/2) and that would give you:
( x / 3 ) + ( 7 / 6 ) = y
You can go one step further and divide the 7 and the 6 and that would give you:
( x / 3 ) + 1.67 = y
Hope I helped!!